Multiple solutions of the BVB for two‐dimensional system by extracting linear parts and quasilinearization - Yermachenko, Inara (Mathematical Modelling and Analysis, 2008)
We investigate a two‐dimensional differential system of the form x’ = f (t, y), y’ = h (t, x) together with the boundary conditions x (0) = 0, x (1) = 0 by using the quasilinearization process. We show that if this problem allows for quasilinearization with respect to essentially different linear parts, then it has multiple solutions. First Published Online: 14 Oct 2010